A call for global governance of biobanks - Chen, Haidan (Bull World Health Organ, 2015)
The progress in genomic research has led to increased sampling and storage of biological samples in biobanks. Most biobanks are located in high-income countries, but the landscape is rapidly changing as low- and middle-income countries develop their own. When establishing a biobank in any setting, researchers have to consider a series of ethical, legal and social issues beyond those in traditional medical research. In addition, many countries may have inadequate legislative structures and governance frameworks to protect research participants and communities from unfair distribution of risks and benefits. International collaborations are frequently being created to support the establishment and proper running of biobanks in low- and middle-income countries. However, these collaborations cause cross-border issues – such as benefit sharing and data access. It is thus necessary to define and implement a fair, equitable and feasible biobank governance framework to ensure a fair balance of risks and benefits among all stakeholders.